Author Correction: Expression-based drug screening of neural progenitor cells from individuals with schizophrenia - Readhead, Benjamin; Hartley, Brigham J.; Eastwood, Brian J.; Collier, David A.; Evans, David; Farias, Richard; He, Ching; Hoffman, Gabriel; Sklar, Pamela; Dudley, Joel T.; Schadt, Eric E.; Savić, Radoslav; et al. (Nature communications, 2018)
In the originally published version of this Article, the affiliation details for Eric E. Schadt and Radoslav Savic incorrectly omitted ‘Sema4, a Mount Sinai venture, Stamford, Connecticut, USA’. This has been corrected in both the PDF and HTML versions of the Article.